Influence of Psycho-Social Factors on Job Performance of Women in the Print Media in Southwestern Nigeria (2014)
Women are now occupying leadership positions regardless of the existing glass ceiling and other barriers. This has however been demonstrated to be having positive impacts on the job performance of the generality of women and especially the print media houses. Previous studies rather than focusing on the psycho-social factors that enhance women‘s performance in the sector, had concentrated more on issues of work-life balancing, leadership and financing. This study, therefore, investigated influence of psycho-social factors on job performance of women in the print media in Southwestern Nigeria. The descriptive survey research design of the ex post facto type was adopted. The stratified and total enumeration sampling techniques were adopted to select 549 women respondents from 12 purposively selected print media. Self-concept Scale (r= 0.83), Self- efficacy Scale (r=0.78), Mentoring Scale (r=0.86), Emotional Intelligence Scale (r=0.69), Social Factors Scale (r=0.93), Job Performance Scale (r=0.85) and Women in the print media Career Progression Checklist were used to determine the influence of psycho-social factors on job performance. These were complemented with 12 sessions of in-depth interviews (IDIs) with selected male line-heads and one female respondent from each of the media houses. Five research questions were answered and four hypotheses tested at 0.05 level of significance to determine the strength of contribution and relationship between the independent and dependent variables. Data were analysed using descriptive statistics, Pearson product moment correlation, multiple regression and content analysis. Psycho-social factors significantly correlated with job performance of women in the print media with (F (9,538) = 82.534) and jointly accounted for about 58.0% of the variance in job performance. Their relative contributions were: psychological factors (β =.427) and social factors (β=.237). Psychological factors correlated to job performance as ranked: Self -concept (r=.535); Self-efficacy (r=.468); mentoring (r=.380) and emotional intelligence (r=.356). Also the social factors correlated with job performance as follows: job entry age (r=.669), socio-economic status (r=.508): educational attainment (r=.481); number of children (r=.240); marital status (r=.185). Further, there was a significant difference in job performance across the print media houses (F(11,537)= 5.678) with mean scores as ranked: Tell Magazine (=71.05); City People (= 70.85); The News (=70.37); Vanguard (=66.16); The Champion (=65.73); The Nation (=65.87); Guardian (=64.00); Daily Sun (=63.70); Punch (=63.06); Tribune (=62.30); The Compass (=61.57) and Business Day (=57.43). Women‘s strength and commitment as well as their desire for self achievement and development were perceived to make them excel on their job. Also, peer mentoring was perceived to have assisted them in discharge of their duties with full sense of accomplishments. Psycho-social factors positively contributed to job performance of women in the print media in Southwestern Nigeria. Priority should be given to these factors while further professional training and good mentoring system be encouraged.